E-cigarette use, its impact on tobacco smoking and the intention to quit - Nurasyikin Mohamad Sapiee; Leelavathi Muthupalaniappen; Tohid H (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
E-cigarettes have rapidly gained worldwide popularity. Since its use still poses a health risk to the users, it is important to assess their intention to quit this habit. This study aimed to determine the characteristics of e-cigarette use, its effect on cigarette smoking and users’ intention to quit vaping and smoking. A total of 377 e-cigarette users were recruited from three vape retail stores in Bandar Baru Bangi, Selangor. E-cigarette usage pattern, tobacco cigarette consumption and their intention to quit were assessed using a self-administered questionnaire. Most (70%) participants were e-cigarettes only users while 30% were dual users. The median duration of e-cigarette use was 2 (IQR 2) years. Almost all (98.4%) participants used third-generation devices and majority (63.7%) preferred liquid containing 6mg nicotine. About 92% participants, especially heavy smokers, smoked fewer tobacco cigarettes after initiating e-cigarette. Majority (79.6%) of dual users also had reduction in tobacco cigarette consumption with a median current consumption of 5 (IQR 5.0) cigarettes per day. Most (87%) e-cigarette users intend to quit the habit someday. However, many (63.1%) were in the pre-contemplation stage. E-cigarette users of less than 2 years duration tend to have the intention to quit compared to users of more than 2 years (p=0.005). In conclusion, there was more e-cigarette only users than the dual users. E-cigarette use could significantly reduce tobacco smoking, especially among heavy smokers. Most e-cigarette users had the intention to quit vaping but not in the near future and longer e-cigarette use may deter their intention to quit.